Making Mala: Malaita in Solomon Islands, 1870s-1930s - Moore, Clive (ANU Press, 2017)
Malaita is one of the major islands in the Solomons Archipelago and has the largest population in the Solomon Islands nation. Its people have an undeserved reputation for conservatism and aggression. Making Mala argues that in essence Malaitans are no different from other Solomon Islanders, and that their dominance, both in numbers and their place in the modern nation, can be explained through their recent history. A grounding theme of the book is its argument that, far than being conservative, Malaitan religions and cultures have always been adaptable and have proved remarkably flexible in accommodating change. This has been the secret of Malaitan success. Malaitans rocked the foundations of the British protectorate during the protonationalist Maasina Rule movement in the 1940s and the early 1950s, have heavily engaged in internal migration, particularly to urban areas, and were central to the 'Tension Years' between 1998 and 2003. Making Mala reassesses Malaita's history, demolishes undeserved tropes and uses historical and cultural analyses to explain Malaitans' place in the Solomon Islands nation today.